Bacterial Leaf Streak of sorghum a new report from India - Navi, S.; Bandyopadhyay, Ranajit; Devi, K.; Reddy, D. (2002)
This paper reports the occurrence of bacterial leaf streak (Xanthomonas campestris pv. holcicola [Xanthomonas vasicola pv. holcicola]) on sorghum (Sorghum bicolor) at the ICRISAT research farm, Andhra Pradesh, India and in several farmers fields in Karnataka in 1999-2001. Disease symptoms were small water-soaked reddish-brown necrotic streaks that later broadened and developed tan centres with a narrow red margin. The bacterium was isolated and confirmed as X. campestris pv. holcicola based on antiserum reactions; this may be the first record of this pathogen on sorghum in India. Attempts to prove pathogenicity of the bacterium by inoculating sorghum seedlings with cultured isolates using various inoculation techniques were unsuccessful.